Students Mistakes Analysis of the Tenth- Grade in Interpretation Verbal Expressions into Algebraic Equations and Quantities - Almassadeh, Kholood Mohammad (Journal of Educational and Psychological Sciences, 2021)
The study aims to detecting the mistakes of the tenth- grade student’s interpretation verbal expressions into algebraic equations and quantities and vice versa, identify and analyze common students’ mistakes. The researcher used the descriptive approach and applied the study to a sample that formed of (100) female students of the tenth grade from Fatima Bint Al Khattab Secondary School, that affiliated to the Directorate of Education for First Zarqa District. A test was prepared - in two models, each model included 3 paragraphs - in phrasing of algebraic equations and quantities and vice versa into verbal expressions and vice versa, and it was applied to two divisions of the tenth- grade. The results have indicated to a classification of students’ most common mistakes at the level of all test items, which were arranged in descending order: Common mistakes in interpretation the verbal phrases of addition, subtraction or multiplication into algebraic symbols: repeated by (39%) within the six test paragraphs, followed by mistakes in mathematical concepts, repeated by (29%), followed by the mistake: Confusion between an equation and an algebraic expression, repeated by (25%). The study also found, through checking the percentages of common mistakes, that the students were unimproved in an interpretation the verbal formulation within a story or phrase into algebraic symbols, or formulating equations or algebraic expressions in a verbal phrase, in a story or a life’s situation. In light of the results, several recommendations were suggested, the most important were as following: Application and execution of the teachers for the teaching strategy by using common students’ mistakes, and the committees based on curriculum development and design should take into account the selection of appropriate words for each age group, when phrasing verbal mistakes, and to ensure that they are linguistically and orthographically correct. Based on the development and design of curricula, choosing appropriate words for each age group, when formulating verbal mistakes, and ensuring that they are linguistically and orthographically correct. It was also proposed to hold training courses for teachers, in order to train them on the use of the developed programs to address common students’ mistakes in mathematics, such as Drive program and Roll Space program.